STRATEGI PENGELOLAAN SAMPAH DINAS LINGKUNGAN HIDUP KOTA YOGYAKARTA DALAM PERSPEKTIF FIQIH LINGKUNGAN - Hidayatullah Hidayatullah (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
The Yogyakarta City Environmental Service implemented a waste management strategy through the Zero Inorganic Waste Movement (GZSA) with initial results in reducing the volume of waste taken to the Piyungan Final Disposal Site (TPA), as well as through the Nitikan TPS3R which is equipped with supporting facilities such as a management office, waste depot, sorting, composting and maggot cultivation area. Inhibiting factors in this strategy include budget limitations, lack of public awareness, and the availability of land for landfills that has exceeded capacity. Efforts to reduce waste entering the landfill are carried out by handling waste according to its type from the source through GZSA, as well as providing outreach to wheelbarrows and residents to sort the types of waste before being disposed of at the TPS/Depo. This waste management is one of the crucial issues in efforts to maintain environmental sustainability. The city of Yogyakarta, as one of the centers of culture and tourism in Indonesia, faces serious challenges related to waste management. From the perspective of Environmental Fiqh, which is a branch of science that studies the relationship between Islam and the environment, there are several strategies that can be implemented by the Yogyakarta City Environmental Service (DLH). In this research, it was concluded that the waste management strategy of the Yogyakarta City Environmental Service in reducing waste entering the Final Disposal Site (TPA), it can be seen that these steps are not just practical policies, but also reflect a commitment to Islamic values ​​in maintaining environment.